Organoids as tools to investigate gastrointestinal nematode development and host interactions - White, Ruby; Blow, Frances; Buck, Amy H.; Duque-Correa, María A. (Frontiers in Cellular and Infection Microbiology, 2022)
Gastrointestinal nematodes are a diverse class of pathogens that colonise a quarter of the world’s human population and nearly all grazing livestock. These macroparasites establish, and some migrate, within host gastrointestinal niches during their life cycles and release molecules that condition the host mucosa to enable chronic infections. Understanding how helminths do this, and defining the molecules and mechanisms involved in host modulation, holds promise for novel strategies of anthelmintics and vaccines, as well as new knowledge of immune regulation and tissue repair. Yet the size and complexity of these multicellular parasites, coupled with the reliance on hosts to maintain their life cycles, present obstacles to interrogate how they interact with the gastric and intestinal epithelium, stroma and immune cells during infection, and also to develop protocols to genetically modify these parasites. Gastrointestinal organoids have transformed research on gastric and gut physiology during homeostasis and disease, including investigations on host-pathogen interactions with viruses, bacteria, protozoa and more recently, parasitic nematodes. Here we outline applications and important considerations for the best use of organoids to study gastrointestinal nematode development and interactions with their hosts. The careful use of different organoid culture configurations in order to achieve a closer replication of the in vivo infection context will lead not only to new knowledge on gastrointestinal nematode infection biology, but also towards the replication of their life cycles in vitro, and the development of valuable experimental tools such as genetically modified parasites.